Ex Vivo Assessment of an Ultrasound‐Guided Injection Technique of the Navicular Bursa in the Horse. (1st December 2015) - Perrin, R.; Diguet, A. C.; Cantet, P.; Bailly, C.; Brogniez, L.; Dugdale, A.; Nisolle, J. F.; Vandeweerd, J. M.
Summary: Synovitis of the navicular bursa is common in performance horses. The objective of this study was to describe an ultrasound‐guided technique to inject a distended navicular bursa and to evaluate its feasibility for use by a clinician not trained in the technique. Twenty distal limbs of horses of various breeds and sizes were used. To produce synovial distension, the navicular bursa of each limb was injected with contrast medium using a lateral approach and radiography was performed to confirm that the contrast medium was distending the bursa. The digit was positioned with the distal interphalangeal joint in hyperextension. A microconvex ultrasound probe was placed in the hollow of the pastern, palmar to the middle phalanx and the region was assessed in a transverse plane slightly oblique to the horizontal plane. The ultrasound probe was rotated to visualize both the lateral and medial recesses and to select which side was more distended to inject. A 21G 0.8 × 50 mm needle was inserted abaxially to the probe in the plane of the ultrasound beam into the proximal recess of this navicular bursa and a methylene blue solution was injected. Following injection, dissection was performed to assess whether the navicular bursa had been successfully injected. This ultrasound‐guided technique was reliably performed with a success rate of 68%. The success of injection is influenced by hyperextension of the foot, quality of ultrasound images and degree of distension of the bursa.